2013
DOI: 10.7596/taksad.v2i2.233
|View full text |Cite
|
Sign up to set email alerts
|

Post-Colonial Analysis of Joseph Conrad’s Heart of Darkness

Abstract: Joseph Conrad's Heart of Darkness tells the journey of Marlow through the African jungle and his search for the European Kurtz who exploits the natives by imposing violence on them. It is mainly based upon Conrad's own experience in Congo when he learned how Europeans exploited and traded the natives for their own benefits during his own journey. The book is regarded as an attack on imperialism and criticizes immoral treatments of the European colonizers in Africa in the 19 th century. Keith Booker states that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…He concluded that Conrad used Wilson Haris' model of layered meaning to highlight the element of destruction and recreation of societies after decolonization. Guven (2013) 7 highlighted the exploitation of colonizers especially the use of violence in Heart of Darkness. He considered that imperialism was the reason for the suppression of the colonized.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He concluded that Conrad used Wilson Haris' model of layered meaning to highlight the element of destruction and recreation of societies after decolonization. Guven (2013) 7 highlighted the exploitation of colonizers especially the use of violence in Heart of Darkness. He considered that imperialism was the reason for the suppression of the colonized.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings of the study show that the author has announced the decolonized culture of America in his work. Güven (2013) carried out a study to analyze Conrad's Heart of Darkness from the viewpoint of postcolonialism. The aim of the researcher is to explore and justify that Conrad has deconstructed the concept of the binary opposition of Europeans, and he did not appreciate the process of colonization.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…It is discussed that one of the causes for savagery in the western conversation in Africa to prevail was to vindicate Africans to be rudimentary, and so, they must be colonized and socialized (Sharmin, 2018, p. 6). Guven (2013) illustrates that when the natives equaled to the Europeans they are viewed as inferior and this is the only reality for them, yet Conrad suggests that this rejected during the novel over after his experiments in Africa disagree with the general doctrine concerning colonialism in England. Marlow is selected by Conrad to illustrate the European colonialism actualities, that is, natives' position told during Marlow, a European as well as.…”
mentioning
confidence: 99%